Transcriptome analysis of flathead grey mullet (Mugil cephalus) ovarian development induced by recombinant gonadotropin hormones - Ramos-Júdez, Sandra; Danis, Theodoros; Angelova, Nelina; Tsakogiannis, Alexandros; Giménez, Ignacio; Tsigenopoulos, Costas S.; Duncan, Neil; Manousaki, Tereza (Frontiers in Physiology, 2022)
Background Treatment with recombinant gonadotropins hormones (rGths), follicle-stimulating hormone (rFsh) and luteinizing hormone (rLh), was shown to induce and complete vitellogenesis to finally obtain viable eggs and larvae in the flathead grey mullet (Mugil cephalus), a teleost arrested at early stages of gametogenesis in intensive captivity conditions. This study aimed to investigate the transcriptomic changes that occur in the ovary of females during the rGths-induced vitellogenesis. Methods Ovarian samples were collected through biopsies from the same five females at four stages of ovarian development. RNASeq libraries were constructed for all stages studied, sequenced on an Illumina HiSeq4000, and a de novo transcriptome was constructed. Differentially expressed genes (DEGs) were identified between stages and the functional properties of DEGs were characterized by comparison with the gene ontology and Kyoto Encyclopedia. An enrichment analysis of molecular pathways was performed. Results The de novo transcriptome comprised 287,089 transcripts after filtering. As vitellogenesis progressed, more genes were significantly up-regulated than down-regulated. The rFsh application induced ovarian development from previtellogenesis to early-to-mid-vitellogenesis with associated pathways enriched from up-regulated DEGs related to ovarian steroidogenesis and reproductive development, cholesterol metabolism, ovarian growth and differentiation, lipid accumulation, and cell-to-cell adhesion pathways. The application of rFsh and rLh at early-to-mid-vitellogenesis induced the growth of oocytes to late-vitellogenesis and, with it, the enrichment of pathways from up-regulated DEGs related to the production of energy, such as the lysosomes activity. The application of rLh at late-vitellogenesis induced the completion of vitellogenesis with the enrichment of pathways linked with the switch from vitellogenesis to oocyte maturation. Conclusion The DEGs and enriched molecular pathways described during the induced vitellogenesis of flathead grey mullet with rGths were typical of natural oogenesis reported for other fish species. Present results add new knowledge to the rGths action to further raise the possibility of using rGths in species that present similar reproductive disorders in aquaculture, the aquarium industry as well as the conservation of endangered species.